854. FRITILLARIA ARIANA: Liliaceae. (April 2017) - Rix, Martyn; Strange, Kit
Summary: Fritillaria ariana (Loz.‐Lozinsk. & Vved.) Rix, is illustrated. The history of its discovery and its cultivation are discussed, and a painting and photograph of the habitat are provided.